Trends and disparities in antenatal care utilization: A multilevel analysis of four-plus and eight-plus ANC visits among urban women in Ethiopia - Heyi, Worku Dechassa; Ayele, Wubegzier Mekonnen; Melesse, Dessalegn Y. (PLOS ONE, 2025)
Introduction Antenatal care(ANC) is the gateway of the continuum of reproductive health care, offering a framework for complication prevention, screening, diagnosis, and health promotion. Objective This study examined trends, disparities and associated factors of ANC utilization (ANC4+ and ANC8+) among urban women in Ethiopia between 2000 and 2019. Methods We analyzed five rounds of Ethiopian Demographic and Health Surveys (2000–2019) data, disaggregated by wealth, education, and region using Stata version 16.1. Multilevel logistic regression model was used to identify factors associated with four-plus and eight-plus ANC utilization. Adjusted odds ratios (AORs) with 95% confidence intervals were reported, with statistical significance set at p < 0.05. Results ANC4 + utilization increased from 43.1% in 2000 to 58.7% in 2019. while, ANC8 + utilization declined from 11.4% to 3.6%. Among the urban non-poor, ANC4 + rose from 60.5% to 81.8% compared to 37.8% to 48.7% among the urban poor. Regional disparities were pronounced: Addis Ababa showed the highest ANC4 + use (72% to 82%), but a decline in ANC8+ (38% to 10%). Somali region had the lowest ANC4+ (9% to 24%) utilization, though it increased from 9% in 2000 to 24% in 2019 and Gambella had the lowest ANC8 + utilization. Wealth disparities were strong, with non-poor women more likely to utilize ANC4+ (AOR= 2.43; 95% CI: 2.12–2.78) and ANC8+ (AOR= 3.02; 95% CI: 2.49–3.65) than poor women. Education also significantly associated: women with secondary or higher education had greater odds of ANC4+ (AOR= 3.02; 95% CI: 2.54–3.59) and ANC8+ (AOR= 2.13; 95% CI: 1.63–2.78). Women aged 30–34 years had higher odds of utilizing ANC4+ (AOR= 2.89; 95% CI: 2.10–3.98) and ANC8+ (AOR= 2.22; 95% CI: 1.37–3.59). Weekly media exposure was positively associated with ANC4+ (AOR= 1.53; 95% CI: 1.28–1.83). Conclusion Significant disparities in ANC (ANC4+ and ANC8+) utilization persist across wealth, education and regions in urban Ethiopia. Wealth status was the strongest predictor, with non-poor women steadily advantaged. Maternal education, age, media exposure, and marital status also showed positive associations, while regional disparities persisted, with Addis Ababa outperforming other urban areas. Improving ANC uptake requires targeted interventions for urban poor women, alongside media-based awareness and educational initiatives.